Promote Folksong Use Game Based On Augmented Reality - Baskara Arya Pranata; Ridwan Sanjaya; Albertus Dwi Yoga W (Soegijapranata Catholic University, 2018)
Abstact- folk songs in indonesia's is wealth cultural heritage most of our ancestors. In this modern era narrower the knowledge of their own folk songs due to the influx of foreign cultures. Augmented is a new technology to display digital visual in the real world. This technology is very interesting when applied in the field of entertainment. This Research Report contains about how to create a game titled Tembang which aims to preserve the songs of the region that originated from the Indonesian. In this game will provide information about the local songs along with their origin, packed in Augmented Reality technology, with challenge quizzes, and there is a gift feature to make players interested in completing the game.